Contesting household debt in Croatia: the double movement of financialization and the fetishism of money in Eastern European peripheries - Mikuš, Marek (Dialectical Anthropology, 2019)
Croatia has experienced a marked boom in household debt in the 2000s. Much of this lending took high-risk and predatory forms that transferred significant risks to debtors, which in turn became the target of contestation by debt activists. This paper uses the Polanyian idea of "double movement" to show how the Croatian debt contestations responded to the distinctively peripheral form of financialization in Eastern Europe, characterized by unequal geoeconomic relationships and an intensified expropriation of debtors. This framework further highlights the importance of money in contemporary credit/debt relationships and their contestation, which has so far received insufficient attention in relevant anthropological scholarship. Instead of the currently fashionable credit theories of money, the paper uses the Marxian concept of the fetishism of money to unpack the roles of money in these processes. The analysis of discourses and practices of two groups of debtors and activists reveals how they used nationalist ideological frameworks and institutional channels such as litigation, again largely ignored by existing anthropological literature, to challenge the particular inequalities of peripheral financialization and the expropriation of debtors through the lenders' predatory manipulations of the money fetish.
Keywords: Croatia; Eastern Europe; consumer credit; contestation; debtor & creditor; financialization; household debt; money

Ritual and Economy: From Mutual Embedding to Non-Profit Festivalisation in Provincial Hungary - Hann, Chris (Ritualas ir ekonomika: nuo abipusės nesuprekintos ekonomikos iki nevyriausybinės festivalizacijos provincinėje Vengrijoje., 2018)
'No human beings, at whatever stage of culture, completely eliminate spiritual preoccupations from their economic concerns' (Malinowski 1935: xx). Drawing on the history and theory of economic anthropology from the pioneering investigations of Bronislaw Malinowski to the work of a postdoctoral research team at the Max Planck Institute for Social Anthropology (Halle/S) between 2009 and 2012, this paper* explores the interface between ritual and the economy in socialist and post-socialist Eastern Europe. The ruptures of early socialism gave way to a re-embedding of the economy that was especially dynamic in the sphere of the household. By contrast, postsocialist disembedding is proving harder to modify. (English)
Keywords: (at)kerėjimas; (dis)enchantment; (po-)socializmas; (post-)socialism; Eastern Europe; Karlas Polanyi; MALINOWSKI, Bronislaw, 1884-1942; POLANYI, Karl, 1886-1964; economic anthropology; ekonomikos nesuprekinimas; ekonominė antropologija; embeddedness; ritual; ritualas; social anthropology; socialism

La Contribución Del Análisis Institucional a Las Ciencias Sociales! - Polanyi, Karl (Revista de Economía Institucional, 2018)
El artículo presenta un discurso del autor en la Conferencia de la Sociedad de Postgrado de Economía de la Universidad de Colombia, Nueva York, en 1950, acerca del análisis institucional a las ciencias sociales. Comenta sobre la relación entre tales ramas de las ciencias sociales como la historia, la economía y la antropología. ENG: The article presents a speech by the author at the Conference of the Graduate Society of Economics of the University of Colombia, New York, in 1950, about the institutional analysis of the social sciences. Comment on the relationship between such branches of the social sciences such as history, economics and anthropology
Keywords: For a New West: Essays 1919-1958 (Book); POLANYI, Karl, 1886-1964; anthropology; anthropology & history; economics; ethnohistory; history & economics; original work; social science research; social sciences

Embeddedness and Effervescence: Political Economy and Community Sociality through a Century of Transformations in Rural Hungary - Hann, Chris (Ethnologie française, 2017)
S’appuyant sur un travail de terrain de longue haleine dans un village de la grande plaine hongroise, l’auteur analyse les liens entre économie politique et formes de sociabilité communément englobées sous le terme de rituel. Trois cycles d’intégration et de désintégration sont décrits. Chacune des phases de déstructuration a conduit à de nouvelles formes d’« auto‑protection » (Karl Polanyi) et à la construction de nouvelles relations communautaires. Les formes exemplaires de sociabilité aujourd’hui sont sensiblement différentes de celles de l’ère socialiste.
Keywords: (post)socialisme; Populisme; Rituel; anthropologie économique; economic anthropology; embeddedness; populism; post-socialism; ritual

Producers' cooperation within or against cooperative agricultural institutions? The case of reindeer husbandry in Post-Soviet Russia - Vladimirova, Vladislava (Journal of Rural Studies, 2017)
With the advance of economic neoliberalization along with the green economy paradigm that aims to alleviate rapid climate change, discussions of the rationale of cooperative organization of food production have come to the fore. This paper contributes to the scholarly understanding of motivations for cooperative organization of production by taking up empirical illustrations from the European North of Russia, where despite expectations of privatization after the dissolution of the Soviet Union, the cooperative organization of reindeer husbandry often persists, as a heritage of the Soviet state enterprises ( sovkhozes ). The paper aims at advancing the analysis of cooperative reindeer husbandry and its rationales employing ideas within the field of substantivist economic anthropology of postsocialism that started with Karl Polanyi's vision of the embedded economy (Polanyi, 1944). Further, I have employed the ideas of the renowned study by Caroline Humphrey of Soviet state farms as total social institutions (Humphrey, 1998) as well as Stephen Gudeman's dialectical approach to the economy (Gudeman, 2001). The analysis shows that the cooperative organization of reindeer husbandry reproduces the economic and social patterns that were developed in the Soviet period, perhaps also adapting and incorporating elements of traditional indigenous social orders. Such social arrangements and the accompanying moral values are embedded in the reindeer herding economy, and it is their persistence that indigenous people achieve through adhering to cooperative values.
Keywords: Eurasian studies; agricultural societies; agriculture - Russia; cooperative organization; embedded economy; farmers & the environment; food production - environmental aspects; reindeer farming; substantivism

An anthropological reading of the policies of international development: export competitiveness as a conjunctural case study - Shakya, Mallika (Dialectical Anthropology, 2017)
Drawing on ethnography of the World Bank's private sector development program, this paper explores the ways in which discussions of export competitiveness emerged in the past decade or so and how they interacted with larger discourses on solidarity and development. The immediate context within which this idea emerged was that of the structural adjustment programs (SAPs) which had maintained that the public regulation of the private economy compromises on industrial productivity (and by extension distributive social justice). But it would be naïve to think that alternative ideologies have not tried to insert themselves within the Bank's neoliberal discourse on development. If anything, discursive narratives suggest that the very notion of export competitiveness initially worked to justify the role of the state in regulating and incubating the private sector in developing countries even if these attempts became disembedded from their local contexts in the long run. This paper contextualizes this specific encounter on export competitiveness within the broader discourse of development and economic anthropology to examine the discursive politics of policy and knowledge in the global aid industry.
Keywords: IFIs; World Bank; anthropology; competition (economics); competitiveness; development; disembeddedness; economic liberalization; embeddedness; ethnology; human economy; structural adjustment program (SAP)

The Anthropocene and anthropology - Hann, Chris (European Journal of Social Theory, 2017)
Noting a lack of consensus in the recent literature on the Anthropocene, this article considers how social anthropologists might contribute to its theorizing and dating. Empirically it draws on the author’s long-term fieldwork in Hungary. It is argued that ethnographic methods are essential for grasping subjectivities, including temporal orientations and perceptions of epochal transformation. When it comes to historical periodization, however, ethnography is obviously insufficient and proposals privileging the last half-century, or just the last quarter of a century, seem inadequate. Influential theories, which define ‘modernity’ in terms of developments emanating from the countries of the North Atlantic in the sixteenth to the nineteenth centuries (Gellner, Polanyi, Wolf), remain partial and Eurocentric. To comprehend the social preconditions of the Anthropocene in a holistic fashion (the crucial contribution of comparative anthropology), it is necessary to follow Jack Goody and trace how the urban revolutions of the Bronze Age united Eurasia through the diffusion of new forms of economy, polity and cosmology.
Keywords: Eurasia; GOODY, Jack, 1919-2015; Hungary; anthropocene; anthropocene epoch; anthropology; cosmology; ethnology; social anthropology; socialism

Moral economy: Rethinking a radical concept - Palomera, Jaime; Vetta, Theodora (Anthropological Theory, 2016)
This article argues that the original thrust of the moral economy concept has been understated and attempts to cast it in a new light by bringing class and capital back into the equation. First, it reviews the seminal works of Thompson and Scott, tracing the origins of the term. It deals with the common conflation of moral economy with Polanyi’s notion of embeddedness, differentiating the two concepts and scrutinizing the ways in which these perspectives have been criticized. Second, it dispels dichotomist conceptions separating economic practice from morality, or embedded configurations from disembedded ones. Against binary views of the market as a boundless realm penetrating previously untainted moral spheres, it posits that social reproduction is characterized by an entanglement of values, which can only be fully grasped by delineating the contours and characteristics of capital accumulation. Third, it contends that moral economy is a dynamic concept because it accounts for class-informed frameworks involving traditions, valuations and expectations. Finally, it argues that moral economy can enrich the concept of hegemony because it pays attention to the often-contradictory values that guide and sustain livelihood practices, through which cultural domination is reproduced or altered.
Keywords: SCOTT, James C.; THOMPSON, E.P.; capital; class; economics - moral & ethical aspects; embeddedness; hegemony; moral economy; saving and investment; social reproduction

Expanding the labor theory of value - Collins, Jane (Dialectical Anthropology, 2016)
This paper revisits debates over the labor theory of value in the 1970s and 1980s and proposes an expansion and revision for the neoliberal era. It draws on three empirical cases of social movements grappling with contemporary changes in the societal division of labor and argues that they can best be understood as 'revaluation' projects seeking to bring recognition to aspects of the economy that are necessary for its long-term sustainability but are not 'counted' as important.
Keywords: division of labor; domestic labor; environment; feminism; labor theory of value; labour theory of value; neoliberalism; public sector; shareholder value; social movements; sustainability

A Concept of Eurasia - Hann, Chris (Current Anthropology, 2016)
To imagine Europe and Asia as constituting equivalent "continents" has long been recognized as the ethnocentric cornerstone of a Western, or Euro-American, world view. The amalgam Eurasia corrects this bias by highlighting the intensifying interconnectedness of the entire landmass in recent millennia. This article builds on the work of Jack Goody and others to analyze the unity-in-civilizational-diversity of the Old World. It draws on the substantivist economic anthropology of Karl Polanyi to postulate continuities between ancient ideals of economic embeddedness in the agrarian empires and various forms of socialism in the twentieth century. Today, when the human economy everywhere is again exposed to the domination of the market, the Eurasian dialectic has universal relevance. However, recognition and realization of pan-Eurasian affinities continues to be impeded by geopolitics, and sociocultural anthropology has a long way to go to overcome its Atlantic bias.
Keywords: Eurasia; GOODY, Jack, 1919-2015; economic anthropology; ethnocentrism; geopolitics; socialism; substantivist

Polanyi'nin Modern İktisatın İnsan Anlayışına Eleştirileri - Akan, Seriyye (Polanyi's Criticisms on Modern Economics' Conception of the Human Being., 2016)
Discipline of economics, who already assimilated the mathematical and technical tools as a base for the expression of theory is almost lost its identity as a social science. This process has become visible through some historical breakups. These breakups have scientific, social and economic faces. While the developments in natural sciences had led the economists to imitate physics - since it uses more certain methods as a science; the market society which established after the industrial revolution separated humans from the economic understanding of the past eras. Rationality, which indeed a philosophical concept, purified from its philosophical context and integrated to economics. On the other hand, the mainstream economics which accepts the maximisation of interest as one of the components of human nature prevailed the economics literature. The modern economics' conception of human had shaped via the steps which we briefly mentioned above. Karl Polanyi (1886-1964) had criticized the human conception of modern economics by using social anthropological methods. He had claimed that market system did not emerged spontaneously, the nature of human did not change throughout history, and primitive economics was totally different from today's market society since the economic relations were embedded in the other social relations. In this article, we tried to analyse Polanyi's criticisms on modern economics' human conception. For this reason, we firstly argued the term rationality in the economic context, since it would be a basis for our subject. Then we emphasized the thesis of "uncahged nature of human" which highlighted by Polanyi, discussions on primitive economies, and the market society which established parallel to the industrial revolution respectively. (English)
Keywords: holism; market society; primitive economies; rationality; social anthropology

"Let Them Eat Stuffed Peppers": An Argument of Images on the Role of Food in Understanding Neoliberal Austerity in Greece - Sutton, David (Gastronomica, 2016)
This paper focuses on how discourses of food have shaped understandings of what is at stake in the Greek crisis. Drawing from Karl Polanyi's concept of "embeddedness," I argue that food is central to Greek interpretations of neoliberal policies and processes because of its centrality to Greek culture and identity. Food has also been a site of contested practices of "solidarity" and "charity" by which new social experiments are emerging in the wake of the breakdown of the welfare state. In arguing for food's centrality in the reshaping of Greek sociability, I will suggest that food be thought of not simply as a "topic" for anthropological investigation, but as a master-concept on the level of "kinship," "ritual," or "exchange" in any anthropological analysis of contemporary life.
Keywords: Greece; Greek crisis; Kalymnos; Oriental and African Studies; austerity (economics); critical food studies; food metaphors; food studies; kinship; neoliberalism; solidarity

Local Trade and Exchange/Employment Systems (LETS) in Future Eco-sustainable Societies - Westra, Richard (Anthropology in Action, 2016)
All communities of practice must face questions relating to the material economic foundations of future sustainable societies. David Graeber, Karl Polanyi and Karl Marx each have produced typologies of possible types of economy, synthesised as: (1) the principle of individual reciprocity, (2) the market principle of capitalism, and (3) the planning principle of the state. I apply this synthesis to recent proposals for community change advanced by Bill McKibben and David Korten concerning economic scale and the re-localising of production and consumption sundered by globalisation, focused on the local exchange and trading system (LETS). The operationalising of LETS draws upon Adam Smith's view of markets as face-to-face exchanges of goods taking place in small morality-bound communities. Smith, McKibben and Korten conflate two different meanings of the term 'exchange'. To understand the role LETS may play in future sustainable economies in communities of practice demands treatment of this problem.
Keywords: MCKIBBEN, Bill, 1960-; capitalism; communities of practice; community; eco-sustainability; economy; globalization; local exchange and trading systems; markets; sustainability; sustainable societies

Goody, Polanyi and Eurasia: An Unfinished Project in Comparative Historical Economic Anthropology - Hann, Chris (History & Anthropology, 2015)
Goody's essay overlaps with his recent work on the “search for metals” and, more generally, with his many books expounding the commonalities of Eurasian history. His critique of Eurocentrism remains invaluable. This review article argues that his emphasis on diffusion can be usefully supplemented with a concept of civilization, to facilitate comparative structural analysis. Goody's perspective might also be enhanced by an engagement with the literature on “Axial Age” cosmologies and with substantivist economic anthropology. It is worth revisiting Karl Polanyi's efforts to grasp the position of the economy in society, in order to recover in the neoliberal present the long-run Eurasian dialectic between redistribution and market exchange.
Keywords: Eurasia; GOODY, Jack, 1919-2015; civilization; culture diffusion; economic anthropology

Migration, Precarization and the Democratic Deficit in Global Governance - Schierup, Carl-Ulrik; Ålund, Aleksandra; Likić-Brborić, Branka (International Migration, 2015)
This article attempts to provide a critical understanding of the dual signification of “precarity”. It explores what “precarity” as a concept may potentially offer to studies of the changing contemporary political economy of migration. It discusses shifting trends in global migration and point to tendencies for a possible convergence between “South” and “North”, “East” and “West”. Based on a review of current advances in research, it discusses, with reference to the classical work of Karl Polanyi, the potential for a contemporary “countermovement” which would challenge the precarity of migrants. Bringing forward the issue of the “space for civil society” the article addresses a still lingering democratic deficit in the global governance of migration. Policy Implications The article is relevant to policymakers, trade unions and civil society organizations. It contributes to the understanding of policy making processes in emerging multilevel global governance and focuses on issues of precarization, migration, and the implementation and accountability of human, migrant and labour rights.
Keywords: countermovement; democratic deficit; ethnicity; global governance; migration; precarity; social welfare studies

After ideocracy and civil society Gellner, Polanyi and the new peripheralization of Central Europe - Hann, Chris (Thesis Eleven, 2015)
Behind only that of Bronislaw Malinowski, the influence of the Central European polymaths Ernest Gellner and Karl Polanyi on socio-cultural anthropology in the 20th century was profound. Gellner and Polanyi also influenced much wider swathes of scholarship. They belong to different generations and were raised in quite different settings in Prague and Budapest respectively. What these thinkers have in common is a philosophy of history which posits the industrial revolution in northwest Europe as a radical rupture in Weltgeschichte. Polanyi’s ‘great transformation’, with its focus on the economy, corresponds to Gellner’s metaphor of the ‘big ditch’ and focus on a new polity. The cultural homogenization of the nation-state and the disembedding of the economy from society in the era of free trade are two sides of the same coin. This paper argues that these complementary models derive to a considerable degree from the scholars’ background on the margins of industrializing Europe, in the ruins of the Habsburg Empire.
Keywords: Central Europe; GELLNER, Ernest; anthropology; civil society

Towards a neo-Polanyian approach to money: integrating the concept of debt - Saiag, Hadrien (Economy & Society, 2014)
This paper aims to reconsider Polanyi's approach to money. His best-known writing on money uses is deeply original and presents strong insights that dissociate money from the concept of the market. Polanyi also developed an interesting non-dichotomous understanding of money in hisThe great transformation. However, taken together, these two contributions lead to some unresolved questions: his critique of the orthodox approach to money is ambivalent; his argument to separate payment from account is weak; and, most important, he ultimately makes an incomplete break with the classical real/monetary dichotomy. This paper proposes a distinction between money as a set of instruments and practices and money as a concept, through the integration of John Commons's concept of debt into Polanyi's framework. This reformulation allows us to resolve Polanyi's unresolved questions while preserving his major contributions, and leads to a more complex understanding of money.
Keywords: COMMONS, J.R.; COMMONS, John; Great Transformation, The (Book); debt; debt management; economic anthropology; economic aspects; economics; money plurality; political aspects; theories of money

The Anthropology of Money and Finance: Between Ethnography and World History - Hart, Keith; Ortiz, Horacio (Annual Review of Anthropology, 2014)
We review here recent developments in the anthropology of money and finance, listing its achievements, shortcomings, and prospects, while referring back to the discipline's founders a century ago. We take our departure from the work of Marcel Mauss and Karl Polanyi, both of whom combined openness to ethnographic research with a vision of world history as a whole. Since the 1960s, anthropologists have tended to restrict themselves to niche fields and marginal debates. The anthropological study of money and ethnographies of finance, in particular, have been the focus of much research since the 1980s. Despite taking on new objects and directions, anthropologists still find it difficult to connect their situated analyses with global processes and world history. We propose some conceptual and empirical directions for research that would seek to overcome these limitations by integrating ethnography more closely with human history, while stressing the importance of money in shaping world society and attempts to reform it.
Keywords: MAUSS, Marcel, 1872-1950; distribution; economic anthropology; ethnology; exchange; finance; globalization; history; money; politics; world society

The Double Movement of Immovable Property Rights in Papua New Guinea - Filer, Colin (Journal of Pacific History, 2014)
Papua New Guinea (PNG) is one of many countries around the world where the relationship between customary land tenure and economic development has been hotly debated for a long time. A commonplace of the debate in PNG is that 97% of the nation's land is held under customary tenure, while only 3% has been alienated, and these proportions have not changed since the country became independent in 1975. This paper shows that the boundary between customary and alienated forms of land or immovable property was already showing signs of instability in the late colonial period, and this instability has been greatly magnified in the post-colonial period. The areas of land subject to some form of partial alienation have increased along with the ways and means by which immovable property has been ‘mobilised’, while a variety of customary claims to previously alienated areas have grown stronger over the same period. Although Karl Polanyi's idea of a ‘double movement’ can throw some light on this phenomenon, the PNG case also reveals a new side to the application of this concept.
Keywords: Papua New Guinea; agriculture; forestry; forests and forestry; land tenure; mineral industries; mining; politics and government; property rights

Three Shades of Embeddedness, State Capitalism as the Informal Economy, Emic Notions of the Anti-Market, and Counterfeit Garments in the Mauritian Export Processing Zone - Neveling, Patrick (Research in Economic Anthropology, 2014)
Purpose -- This paper furthers the analysis of patterns regulating capi-talist accumulation based on a historical anthropology of economic activ-ities revolving around and within the Mauritian Export Processing Zone (EPZ). Design/methodology/approach -- This paper uses fieldwork in Mauritius to interrogate and critique two important concepts in contemporary social theory -- "embeddedness" and "the informal economy." These are viewed in the wider frame of social anthropology's engagement with (neoliberal) capitalism. Findings -- A process-oriented revision of Polanyi's work on embedded-ness and the "double movement" is proposed to help us situate EPZs within ongoing power struggles found throughout the history of capital-ism. This helps us to challenge the notion of economic informality as supplied by Hart and others. Social implications -- Scholars and policymakers have tended to see eco-nomic informality as a force from below, able to disrupt the legal-rational nature of capitalism as practiced from on high. Similarly, there is a view that a precapitalist embeddedness, a "human economy," has many good things to offer. However, this paper shows that the practices of the state and multinational capitalism, in EPZs and elsewhere, exactly match the practices that are envisioned as the cure to the pitfalls of capitalism. Value of the paper -- Setting aside the formal-informal distinction in favor of a process-oriented analysis of embeddedness allows us better to understand the shifting struggles among the state, capital, and labor.
Keywords: Mauritius; capitalism; economic anthropology; embeddedness; embeddedness (socioeconomic theory); ethnohistory; export processing zones; informal sector (economics); neoliberalism

Responding to the crisis: food co-operatives and the solidarity economy in Greece - Rakopoulos, Theodoros (Anthropology Southern Africa (Anthropology Southern Africa), 2013)
This article discusses a case of popular social response to imposed austerity and recession in Greece. It focuses on the anti-middleman movement in an Athens suburb. It also addresses the broader picture of the current Greek crisis, explaining how participants in this grassroots response extend their activity beyond food distribution, beginning to imagine modes of economic conduct and interaction different from those currently dominant in Greece. I explore their efforts to turn the food market they have established in Athens into a formal co-operative which links consumers in their neighbourhood directly to selected farmers through bonds of solidarity, and to work with others to create a network of similar co-operatives which will span the whole country. I argue that their endeavours strongly resemble the co-operativism and practical socialism advocated by important social theorists such as Mauss and Polanyi, and suggest that it may be important for the young activists in Athens to learn more about their ideas.
Keywords: Greece; Greek crisis; MAUSS, Marcel, 1872-1950; anthropological research; anti-middleman movements; economic development; financial crises; financial crisis; food co-operatives; food industry; horizontal co-operative networks; recessions; solidarity economy; sovereign debt crisis

Towards a human economy: reflections on a new project - Sharp, John (Anthropology Southern Africa (Anthropology Southern Africa), 2013)
The University of Pretoria's Human Economy project began at the end of 2010. To date it has involved eighteen post-doctoral fellows, drawn from around the world, and eight doctoral candidates, all from Africa. This paper reviews the project's progress, drawing attention to how its participants have come to construe the notion of a 'human economy' and the main social theorists on whom they have drawn in doing so. The development of our thinking regarding a human economy is explained by reference to the two edited volumes, comprising contributions from all the post-doctoral fellows, which will be published in the near future. Challenges for future research are considered in the final part of the paper.
Keywords: MAUSS, Marcel, 1872-1950; South Africa; University of Pretoria; doctoral degree; economic development; human economy; market exchange; mutuality; plural economy; reform; revolution; social development; social sciences

Karl Polanyi - Le père de la socioéconomie - Journet, Nicolas (Les Grands Dossiers des Sciences Humaines, 2013)
Penseur au parcours très singulier, Karl Polanyi est l’un des fondateurs d’une discipline nouvelle, l’anthropologie économique, qui se consacre à l’étude des échanges dans les sociétés anciennes et ambitionne de théoriser, à l’échelle de l’humanité, ce qu’il en est des rapports entre société et économie.?Pourtant, son œuvre la plus célèbre, La Grande Transformation, ne sort pas du cadre de l’histoire... Plan of the article: Radical liberalism versus social life The free market: an intolerant doctrine An argument against neoclassical orthodoxy
Keywords: free market; neoclassical economics; radical liberalism

Interests, Resources and Status: The Distribution of Income, Work and Authority in the Family in a Northern Hungarian Village - Sárkány, Mihály (Acta Ethnographica Hungarica, 2013)
The author deals with two interconnected features of contemporary Hungarian rural family life from a historical perspective based on fieldwork carried out in Varsány in the early 1970s and between 2000 and 2005. The first is the intertwining of the lives of successive generations of families in a period when other segments of Hungarian society were becoming more individualistic. This case puts into question whether economic models of the direction of the flow of goods between generations (linear, altruistic or exchange models) are applicable for this situation. The author suggests that Polányi's ideas may be of help in understanding this phenomenon. The second is the balance of genders within families. Tatjana Thelen, who did fieldwork in another Hungarian village, Mesterszállás, pointed out a decline in the status of women. She holds the Hungarian policy of privatisation and reprivatisation responsible for it, which followed the great socio-economic and political change from socialism to capitalism in 1990. As a similar decrease in the status of women did not occur in Varsány, the author argues that other factors also should be taken into consideration for analysing such situations, like the role of commuting, education, and women's share in landed property.
Keywords: Hungary; authority; distribution (economic theory); families; gender; generation; income distribution; research; rural family; transfer of income; work

Processes of disembedding and displacement: anomie and the juridification of religio-ethnic identity in post-New Order Bali - Ramstedt, Martin (Asian Ethnicity, 2012)
This article applies Karl Polanyi's observation of a double movement of law in the history of nineteenth and early twentieth-century Europe to an analysis of Bali's integration into the global cultural economy. It describes how the increasing disembedding of the island's tourist industry from local norms and institutions, and the parallel disjuncture between Balinese religiosity and Indonesian state religion have created a condition of increasing collective anomie that has in turn provoked endeavors to juridify the Balinese religio-ethnic identity. Conceding the partial success of the juridification process that has been facilitated by the recent governance reform, and that has indeed effected a significant degree of re-embedding both tourism and religion into local culture, the article argues that not only has the anomic condition not been attenuated; the potential for internal conflict and division has even been enhanced.
Keywords: Bali; Balinese (Indonesian people); Europe; POLANYI, Karl, 1886-1964; anomie; decentralization; decentralization in government; disembedding; ethnicity; identity; juridification; religiousness

The roots of the global economic crisis (Respond to this article at http://www.therai.org.uk/at/debate) - Hart, Keith (Anthropology Today, 2012)
The world economic crisis should be seen as an episode in the history of money. “National capitalism” was the main way of organizing money in the twentieth century and its symbol was national monopoly currency. This system has been unravelling since the US dollar de-pegged from gold in 1971. The result is a disconnect between politics which are still largely national and the money circuit which is decentralized and global. The work of Georg Simmel and Karl Polanyi is enrolled to explain this development which entails the loss of money's physical substance, a shift in the social institutions supporting it and a break-up of the forms and functions of “all-purpose money”. The euro crisis reveals the historical mistake of treating market economy as a driver of society and politics. Good intentions at this stage will not reverse what has become a Greek tragedy in more senses than one.
Keywords: global economic crisis

Nature, Capital and Neighborhoods: 'Dispossession without Accumulation'? - Kappeler, Aaron; Bigger, Patrick (Antipode, 2011)
The ongoing economic crisis, which originated in the USA and has since spread rapidly to capital markets worldwide, is massive, complex, and many times contradictory. One could say the same for responses to the crisis as governments, firms and multi-national institutions struggle to grasp the full magnitude of the event. This article interrogates the key commodities involved-land, labor and money-and the always-uneasy relations between spaces of social reproduction and capital. Such ambivalence is critical to understanding how new economic realities are formed in light of retreating neoliberalism as markets become destabilized. The analysis provided suggests the commodities involved in the housing crisis are the basis for a countermovement against dispossession.
Keywords: MARX, Karl, 1818-1883; United States; capital market; capitalism; housing market; international business enterprises; labor; labour; mixed economy; neoliberalism; social aspects

The Commodification of Pollution and a Preemptive Double Movement in Environmental Governance: The Case of Water Quality Trading - Mariola, Matt J. (Organization & Environment, 2011)
The management of environmental pollution has traditionally been accomplished via the regulatory power of the state, but more recently the rise of a new, market-based form of governance has been observed. This article examines the sector of water quality trading, in which caps are placed on surface water pollution and polluters can purchase “offset credits” from farms or other polluters who are under their cap. Using a content analysis of program case studies and federal and state trading rules, the author analyzes this emergent form of environmental governance using an expanded Polanyian framework that he terms the preemptive double movement. Instead of the state reacting to the dangers of a new market form after the fact, here the state uses its existing authority to constrain the market so that further environmental damage does not result. The author describes eight specific regulatory mechanisms that illustrate this preemptive double movement at work.
Keywords: Polanyi; business & the environment; commodification; double movement; ecological impact; nutrient trading; pollution; water quality management; water quality trading

Redistribution in Aegean Palatial Societies Redistribution and the Political Economy: The Evolution of an Idea - Earle, Timothy (American Journal of Archaeology, 2011)
Whether the Bronze Age Aegean economies can be described as "redistributive" depends on how one defines the term. The concept of redistribution itself has undergone several decades of critical archaeological analysis, much of it stemming from my early work in Polynesia. I consider here how Polanyi's ideas about redistributive economies have been expanded since the 1970s. My review complements the article in this Forum by Nakassis et al. and the contribution by Haistead, who discusses why and how the concept of redistribution still matters in studies of the Minoans and Mycenaeans. To some degree, we all agree: chiefs, and later kings, who sought power in archaic societies did so through many highly variable, contingent, and changing means, all designed to support political-economic strategies based on multiple systems of finance. The Bronze Age Aegean societies provide excellent examples of this process, as demonstrated by the contributors to this Forum.
Keywords: Aegean civilization; Bronze age; chiefdoms; economic aspects; kings & rulers; metals; redistribution; wealth

Redistribution in Aegean Palatial Societies Redistribution in Aegean Palatial Societies: Terminology, Scale, and Significance - Halstead, Paul (American Journal of Archaeology, 2011)
Nakassis et al., in their contribution to this Forum, argue that the term "redistribution" has been used with a range of meanings in the context of the Aegean Bronze Age and so obscures rather than illuminates the emergence and functioning of political economies. They call for detailed empirical investigation rather than reliance on ambiguous idealized types. Lupack and Schon concur, arguing respectively that the palace shared control of the Mycenaean economy with sanctuaries and local communities and that centralized production of craft goods (an,d thus elite strategies of wealth finance) developed late at the palace of Pylos. Pullen finds little archaeological support for Renfrew's extrapolation of centralized redistribution to the Early Bronze Age, while Christakis uses evidence of storage to argue the same for Prepalatial Crete and to play down the scale and importance of elite redistribution in the Minoan palaces. The calls for circumspect use of the term "redistribution" and for detailed empirical investigation are applauded, although these five papers arguably do not all attack the same form of redistribution. This response argues that redistribution sensu Polanyi, Finley, and Killen (i.e., centrally administered movements of goods and services without equivalence of value) retains considerable heuristic value in investigation of both textual and archaeological evidence for Bronze Age political economies.
Keywords: Aegean civilization; Eleia (Greece); Greece; Mycenaean civilization; Pylos site (Eleia, Greece); archaelogy; bronze age; economics; redistribution

The Aporia of Power: Crisis and the Emergence of the Corporate State - Kapferer, Bruce (Social Analysis, 2010)
The argument focuses on the corporate state as an increasingly significant political assemblage that has enabled new configurations of power with related social effects. Here the discussion proceeds from Karl Polanyi's thesis in The Great Transformation. A critical idea that Polanyi pursued related to the state production of economism and individualism, which prepared the ground for the expansion of capital in its globalizing form. The essay develops this idea, indicating that the nationalist capitalism of the state led to a radical change in the political and social orders of states, gradually giving rise to the corporate state assemblage. The emphasis here is on the corporate state as a socio-political order that places radically distinct structural dynamics into impossible conjunction, leading to progressively disastrous social effects concerning poverty and the emergence of new configurations in which war and violence take specific shapes.
Keywords: Great Transformation, The (Book); bureaucratic processes; corporate state; crisis; economism; globalization; individualism; nation-state; poverty; power (social sciences); reterritorialization; violence; war; war machine

Polanyian meditations on economy and society: a review of 'Market society: the great transformation today' - Dale, Gareth (Dialectical anthropology, 2010)
Keywords: book review; cultural ethnography; economic anthropology; market economy; society

Performing economy differently: Exploring economic personhood and local economic diversity - McKay, Deirdre (The Australian Journal of Anthropology, 2009)
Many popular conceptions of economy now delimit what counts as the ‘real’ economy by capitalist enterprises, market transactions and wage labour. Anthropologists describe such ideas of economy as abstract, dis-embedded (Polanyi 1957a, b) or virtual (Carrier and Miller 1998), arguing that these conceptions are not adequate to the empirical realities of lived experience. Beyond anthropology, there is a growing literature that theorises the ways academic accounts have themselves brought a dis-embedded or virtual version of economy into being (Mitchell 2002, 2008; Callon 2005; Callon and Caliskan 2005; Latour 2005; Gibson-Graham 2006). Scholars advocating a performative approach argue that academic notions of economy are not simply descriptive of empirical realities, but actively shape those realities, giving form to the ways that a ‘real’ economy emerges from particular socio-cultural fields. In the context of applied development anthropology, a performative reading of economy offers a helpful platform for applied research directed towards diversifying local economic understandings and practices. This paper explores the implications of performing economy differently through reflections on an action research project undertaken in the Philippines. Here, a performative approach recreated economy as a space of decision that demands active, ethical choices (Gibson-Graham 2006) and supported relational, rather than individuated, models of economic personhood.
Keywords: action research; disembeddedness; economic anthropology; performative approach

The Athenian Economy in Light of the Welfare State: Karl Polanyi's Work in Perspective - Wjuniski, Bernardo Stuhlberger; Fernández, Ramón García (Journal of Economic Issues (Taylor & Francis Ltd), 2009)
Karl Polanyi considered that the relationship between the markets and their societies was a central feature of any social order. He studied what he called "ancient societies," to compare them with his own times, in an effort to understand that subject This paper aims to show, following Polanyi's work on Classical Greece, that it is possible to make a clear analogy between the Athenian state and economy with the modern Welfare State. First, we present Polanyi's study of the early Athenian economy, focusing on the coexistence of a kind of state economic planning and a market Second, we show how this relates to Polanyi's emphasis in the comparison of different societies and times. Third, we characterize the contemporary Welfare State to make an analogy between these two forms of economic organization. We conclude by underlining the relevance of this analogy in understanding the societies of today.
Keywords: Athenian supremacy, Greece, 479-431 B.C.; Athens (Greece) - history; Greece; Polis (the Greek word); classical Greek economy; economic anthropology; economic policy; embeddedness; equity; history of economics - to 1800; imperialism; markets - social aspects; money; social order; welfare state

Exchange networks and free shops in Berlin: gifts and commodities in ‘alternative’ consumption experiences - Sabaté Muriel, Irene (Etnográfica. Revista do Centro em Rede de Investigação em Antropologia, 2009)
This paper is based on an ethnography of ‘alternative’ consumption practices in the inner city of the former East Berlin. Non-monetary exchange networks (Tauschringe) and ‘free shops’ (Umsonstläden) have been examined. In Umsonstläden, the contemporary ideology of the ‘pure’ gift (Parry 1986; Carrier 1995) is at play: objects are freely given and totally alienated from their owners. In turn, Tauschringe sometimes induce gift-giving practices entailing mutual obligation, as a result of frequent exchanges which bring participants socially closer. The ethnographic material I present challenges the suitability of a conceptual gift / commodity divide to examine these experiences, provided that different modalities of gift-giving are articulated with commoditisation trends. Considering this complexity, I propose a re-examination of the role of the gift in ‘alternative’ consumption practices promoted by social movements in Berlin., O artigo baseia-se numa etnografia de práticas de consumo “alternativas” nos bairros centrais da antiga Berlim-Leste. São aqui analisadas as redes de intercâmbio não monetário (Tauschringe) e as “lojas gratuitas” (Umsonstläden). As Umsonstläden são enquadradas pela ideologia contemporânea da dádiva “pura” (Parry 1986; Carrier 1995): os objectos são dados gratuitamente e totalmente alienados dos seus possuidores. Já as Tauschringe, por seu lado, induzem por vezes práticas de oferta que implicam obrigações mútuas, como consequência de trocas frequentes que aproximam socialmente os participantes. O material etnográfico apresentado põe em causa a adequação do binómio dádiva / mercadoria à análise dessas experiências, na medida em que diferentes modalidades de oferta se conjugam com tendências para a mercadorização. Face a essa complexidade, o artigo propõe uma revisão da análise do papel da dádiva em práticas de consumo “alternativas” promovidas pelos movimentos sociais em Berlim.
Keywords: Berlin; consumption; economic anthropology; embeddedness; exchange networks; fallacy of the market; free shops; gifts/commodities; social economy; social movements

Economics, Anthropological Models and the Ancient Near East - Warburton, David A. (Anthropology of the Middle East, 2009)
This article discusses the evidence of markets in the Ancient Near East. The major points are (1) the shortcomings of the misguided application of the Polanyi model and (2) the ensuing implications of the failure to integrate economic history into modern economic theory. The analysis concentrates on Ancient Egypt, as it presents the most significant problem for economic history and theoretical modelling. Detailed criticism of the means by which the Polanyi model is upheld is coordinated with an argument in favour of recognising the importance of markets. The argument is that these markets are relevant both to long-term economic history and to modern economic theory – and that this must lead to a new debate about ancient and modern economies.
Keywords: Egypt; Middle East; ancient civilization; anthropology; economic history; economic theory; economics; markets; neo-classical synthesis; technology

Anthropology in the financial crisis - Hart, Keith; Ortiz, Horacio (Anthropology Today, 2008)
This editorial considers the opportunities opened up for anthropologists by the financial crisis of 2008. The chief of these is the exposure of cracks in the intellectual hegemony of free-market economics which contributed to an unnecessarily defensive posture on the part of most anthropologists during the period of neoliberal globalization. The authors claim that anthropology can bridge the gap between everyday life and the world at large by combining the study of ideas and social actions. We draw on Ortiz's research among financial professionals to show how working practices informed by economic liberalism can have extremely unequal consequences for the global distribution of resources. The perspectives of Mauss and Polanyi on political economy can help us to make sense of the current situation and to recommend a path forward beyond market fundamentalism. Their general ideas lend power to the concrete findings of field research. The mask of neoliberal ideology has been ripped from the politics of world economy. Anthropology's highest mission is to start from where people are and go with them wherever they take you. What better time to follow this imperative than when the model the world has been compelled to live by for three decades is in such disarray?
Keywords: finance; financial crisis

Karl Polanyi's Legacy - Hart, Keith (Development and Change, 2008)
Click on the article title to read more.
Keywords: biography

La dépolitisation de la notion de « capital social » : pourquoi pas un retour à Karl Polanyi? - Bibeau, Gilles (Anthropologica, 2008)
Keywords: social capital

After the disaster - Hart, Keith (Anthropology Today, 2008)
Naomi Klein's The Shock Doctrine offers a weak analysis of ‘neoliberalism’ linked to a defeatist ideology. If we wish to move beyond the global economic crisis, we should borrow ideas from Mauss, Polanyi and Keynes; but the political level for an appropriate response is not obvious.
Keywords: KLEIN, Naomi; neoliberalism

Karl Polanyi and the antinomies of embeddedness - Gemici, Kurtuluş (Socio-Economic Review, 2008)
While Polanyi argues that all economies are embedded and enmeshed in social relations and institutions, he tends to see market economy as disembedded, which reveals a tension in his thought. The main motivation for this paper is to understand the origins of this tension. On the basis of a systematic formulation of Polanyi's work, it is argued that Polanyi employs embeddedness in a dual manner: (a) as a methodological principle akin to methodological holism, and (b) as a theoretical proposition on the changing place of economy in society. These two formulations of embeddedness contradict each other. After tracing out the origins of this contradiction, this paper concludes by considering the implications of this analysis for economic sociology. It is argued that embeddedness as a methodological principle is the only acceptable usage of the term. Yet, in this capacity, embeddedness falls short of economic sociology's goal of providing a theoretical alternative to neoclassical economics.
Keywords: Austrian history of economic thought; cultural economics; economic anthropology; economic sociology; economic systems; embeddedness; evolutionary; historical; institutional; relation of economics to other disciplines

Licenciements collectifs : le prix d'une dette symbolique, Massive Layoffs : The Price of a Symbolic Debt - Malsan, Sylvie (Revue du MAUSS, 2007)
Les licenciements massifs que connaît depuis vingt ans l’industrie française conduisent les ouvrier(ière)s à exprimer des demandes de réparation symbolique sous des formes nouvelles, dont l’interprétation échappe au paradigme classique de la lutte des classes. C’est avec Karl Polanyi, pour qui l’activité économique n’est pas autre chose que la vie elle-même, et Marcel Mauss, qui a posé le don au centre des relations sociales, que nous tentons de réinterroger la relation de travail dans son inégalité constitutive, mais aussi dans ce qu’elle représente pour l’ouvrier(ière) comme don de soi. En nous appuyant sur les données empiriques d’une enquête menée dans la région de Cherbourg, nous entendons caractériser le lien symbolique existant au coeur même du contrat de travail., ENG: Massive layoffs have occurred during the last twenty years in French industry which brings workers to express demands for symbolic reparation under new forms. This phenomena cannot be interpreted by classic paradigms as class struggles. Here we try to analyse working relationships through Polanyi and Mauss approaches. The first one considers that economic activity is nothing else that life itself ; the second puts gift at the core of social relationships. Following these authors, we characterize the symbolic link between employer and employee, which is anchored into employment contract. Our empirical data are based on research carried on in Cherbourg’s area (France).
Keywords: France; labour; symbolic debt

Postoji Li Mogućnost Instaliranja Socijalnog Kapitalizma U Post-Socijalističkoj Tranziciji? - Lošonc, Alpar (Is It Possible to Install Social Capitalism in Postsocialist Transition?, 2007)
Recently Claus Offe has raised the question concerning the fate of the European model of social capitalism. Can the model of social capitalism survive European integration amongst current tendencies? Offe assumes that this model has been challenged by the processes of globalisation and by the integration of postsocialist countries into the European Union. The working hypotheses of this article is that a relatively coherent answer to this question may be offered. The article is divided into three parts. The first part starts with Polanyi's socio-economic theory and emphasizes the importance of this approach for analyzing tendencies of capitalism in Western Europe and in post-socialist countries. The author argues that Polanyi's theory enables us to explain the forms of embedded liberalism in Western Europe after 1945, as well as the orientation of non-embedded neoliberalism and the functioning of the workfare state after the crisis of the Keynesian welfare state. The central element of social capitalism, namely, the welfare-state, despite globalizing tendencies projected by neoliberalism, still has dimensions of continuity. In the second section it is argued that an asymmetrical structure has arisen between Western Europe and the non-Western part of Europe concerning the socialisation of capitalism. Neoliberalisation in accordance with the model of transferring ideal-type capitalism is much more strongly implemented in transition countries. In the third part the author pleads for a broadening of the meaning of welfare to take into account the ecological aspect of welfare in countries in transition. The author insists that embeddedness must also include socio-ecological aspects of transition processes in postsocialist countries. Moreover, this theoretical approach provides an opportunity to explain the failures in implementing neoliberalism in postsocialist countries. If we introduce socio-ecological aspects we are in a much better position to answer Offe's question. (English)
Keywords: Europe; OFFE, Claus; capitalism; država blagostanja; neoliberalism; social anthropology; social capitalism; social psychology; socijalni kapitalizam; socio-ecological embeddedness; socio-ekološka utkanost; transition; tranzicija; welfare state

The End of Potlatch: An Anthropological Approach to Nostromo - Juhász, Tamás (Research in Economic Anthropology, 2007)
This study contends that the various forms of archaic trade that anthropologists have reconstructed on the Northwest Coast of America are explanatory of plot-construction and characterization in Conrad's South-American novel. My thesis is that Nostromo is a figure defined by the practice of potlatch, and that his key presence in the plot entails the representation of a culturally dislocating transition from archaic transactions to modern commerce. The theoretical framework of this chapter hinges on the insights of Marcel Mauss, Claude Lévi-Strauss, Karl Polanyi, and Georges Bataille.
Keywords: CONRAD, Joseph; LEVI-STRAUSS, Claude; Nostromo (book : Conrad); archaic economy; embeddedness; history of commerce; plots (Drama, novel, etc.); potlatch; reciprocity; redistribution

Editor's Letter - Lomnitz, Claudio (Public Culture, 2006)
This article previews this edition of "Public Culture" and focuses on Karl Polanyi's theories on capitalism. Polanyi believed in trade liberalization and felt that market regulation is the principal obstacle to collective prosperity. He thought that unregulated markets could bring an end to poverty, and would resolve the chronic dislocation, inequality, and vulnerability that have marked capitalism from its inception. Polanyi demonstrated that market liberalization was only achieved through concerted state intervention.
Keywords: capitalism; free trade; intervention (federal government); poverty; public culture (periodical)

From flows to violence - Kalb, Don (Anthropological Theory, 2005)
Recent globalization theory reflected a chain of world historical events since the end of the Cold War. Globalization theories were tools for the making of political alliances between market liberals and political, liberals. From the mid-1990s a broad range of institutionalist social science programs showed that globalization outcomes were often better explained by institutional logics (including cultural ones) than by global flows per se. This is, among others, illustrated by the debate on global inequality data. The emerging debate on empire and imperalism is discussed as a logical offshoot of the globalization discussion just as the phenomenon itself is seen as a likely outcome of an epoch of market-driven globalization. Globalization was predicated on the emergence of a US-led transnational western state structure on behalf of the transnational capitalist class based in finance and the large corporations. Territory and space have become more important rather than less, but the explanation of regional trajectories must now be located more firmly in the interaction between local and global structures. This leads to a new agenda in the social sciences: one oriented toward common interdisciplinary programs with a limited range of core questions - about state formations, class formations, mobilizations, claim making, and associated cultural processes. Programs should be more theory driven, comparative, and in search of explanations of divergent spatial and temporal outcomes of universal process.
Keywords: alliances (international relations); civilization; cultural policy; dual polarization; empire; globalisation; globalization; imperialism; international relations; social sciences & state; transnational capitalist class

Economics and the Space of Modernity: - Escobar, Arturo (Cultural Studies, 2005)
This text was the original second chapter of the author's doctoral dissertation (Escobar 1987); this chapter was never included in the book that eventually grew from the dissertation (Escobar 1995). Although the chapter's contribution to debates on the economy are largely synthetic and certainly not original, the author wanted to publish it for a number of reasons. First, the alleged triumph of neo-liberal ideologies and the increase in depth and scope of market cultures at present make even more important the task of cultural analysis of economics and the economy. This paper was an effort in this direction, particularly to mapping the genealogies of what in the paper is called ‘the Western economy’. Second, there have been some recent claims that the cultural analysis of economics and the economy has hardly been broached. References to Polanyi's foundational role in this respect are, of course, de rigueur, but one only needs to point at the pioneering work of Stephen Gudeman since the 1980s to dispute this claim. Third, the same cultural analysis is experiencing a much needed surge, with several groups today fully engaged with it from various – some times overlapping – perspectives. Finally, the impetus for this piece also comes from the creative efforts by a number of social movements in the world – such as some of the autonomistas in Argentina – to go even beyond ‘rethinking’ the economy to propose that what is needed is a new invention altogether.
Keywords: anthropology of modernity; cultural studies; cultures of economy; economic history; economics; genealogy; modernity; resistance; social history; third world

Student Labor and Evolution of Education - Sidorkin, Alexander M. (World Futures: The Journal of General Evolution, 2004)
The evolution of teaching is examined in three stages: apprenticeship, classical schooling, and mass schooling. All three stages use different social technologies to operate. The mass schooling is analyzed from the point of view of economic anthropology developed by Karl Polanyi, as a non-market economic system. Mass schooling uses the forms of motivation found in archaic, tribal economies: students do their homework and attend school out of considerations of reciprocity. Schools must be treated differently with respect to their improvement. School improvement should be based on perfecting existing non-market economic mechanisms, not on plunging schools into market economy.
Keywords: POLANYI, Karl, 1886-1964; apprenticeship programs; economic anthropology; education; educational anthropology; evolution of education; motivation in education

Polanyi and the Peasant Question in China: State, Peasant, and Land Relations in China, 1949–Present - Chuang, Julia; Yasuda, John (Politics & Society, 2022)
This article applies Karl Polanyi’s concept of a double movement to the trajectory of rural state policies in China since 1949. It argues that Chinese socialism created a contradictory social contract that has fueled an ongoing struggle between state and peasantry over the surplus generated from rural land. This struggle has shaped a historical oscillation between state policies that facilitate extraction of agricultural surpluses and policies that introduce social protections in the form of household farming and revitalized collective ownership. Based on secondary sources, this article compares the arc of rural policies during the Mao era and in the transition to and during the current state capitalist period. Then, based on original interview-based and ethnographic fieldwork undertaken in rural Sichuan Province, it analyzes the current introduction of urban and agrarian capital into the rural economy, revealing dynamics of a current countermovement from state-led extraction to compromise.
Keywords: China; Polanyi; agrarian transition; land politics; peasant politics; state capitalism; urbanization

Neoliberal Capitalism and Visegrád Countermovements - Hann, Chris; Scheiring, Gábor (Europe-Asia Studies, 2021)
Keywords: countermovement; populism; visegrad countries

MERCADOS E PRAÇAS DE MERCADO: KARL POLANYI E O CAPITALISMO CONTEMPORÂNEO - Parpet, Marie France Garcia (Sociologia & Antropologia, 2021)
Resumo Explorando as distinções conceituais entre mercado, sistema de mercados formadores de preço e praça de mercado, concebidas por Karl Polanyi, o artigo mostra a pertinência dessas diferenças para a análise do capitalismo contemporâneo, ao focalizar a caracterização e os efeitos específicos de praças de mercado da atualidade. Evoca a contribuição de Polanyi para repensar o conceito de mercado tal como referido na literatura econômica e especificar a historicidade dos mercados, sobretudo do sistema de mercados formadores de preço (equivalente de sistema capitalista), opondo esses conceitos a praças de mercado. Recorre a trabalhos etnográficos e/ou sociológicos, sobre praças de mercado contemporâneas, verificando que elas existem nas configurações atuais das trocas mercantis e podem criar valor simbólico e material, estando na origem de processos de diferenciação social, intensificados, por exemplo, no caso das plataformas digitais.
Keywords: Karl Polanyi; Mercado; institucionalização; plataformas digitais.; praça de mercado; salões de exposição; sistema de mercados

CAPITALISM, DEMOCRACY, AND SOCIAL THEORY IN KARL POLANYI: AN INTERVIEW WITH GARETH DALE - Santos, Rodrigo Salles Pereira dos; Onto, Gustavo Gomes (Sociologia & Antropologia, 2021)
Resumo Uma introdução à entrevista realizada com Gareth Dale (Brunel University) − economista político e especialista na trajetória e na obra de Karl Polanyi − e a um conjunto de textos inspirados na abordagem polanyiana publicados neste número de S&A. Recupera questões-chave apresentadas na entrevista e na obra de Dale, dando relevo à literatura recente produzida sobre o autor, à contínua e difundida relevância das ideias de Polanyi para a compreensão do capitalismo e da democracia, e a uma leitura crítica e aberta de suas contribuições teóricas. Divulga as contribuições específicas, teóricas e empíricas, de quatro artigos originais que mobilizam ativamente conceitos polanyianos no entendimento da pluralidade dos processos de enraizamento e das dinâmicas do movimento duplo, de mercantilização da terra e do trabalho, e da centralidade da praça de mercado no capitalismo contemporâneo; além dos aportes de um registro de pesquisa e duas resenhas sobre agências e pedagogias econômicas e financeirização da vida cotidiana. An introduction to the interview with Gareth Dale (Brunel University) − a political economist and expert on Karl Polanyi’s life and work − and to a set of papers, inspired by the Polanyian approach, published in the current issue of S&A. The paper highlights key questions presented in the interview and in Dale’s work, with a focus on the recent literature produced about the author, the continuous and widespread relevance of Polanyi’s ideas for the understanding of capitalism and democracy, and a critical and open reading of his theoretical contributions. Next, the paper presents the specific contributions, both theoretical and empirical, of four original papers that actively dip into Polanyian concepts in understanding the plurality of the embeddedness processes and the dynamics of the double movement, the commodification of land and labor, and the centrality of the marketplace in contemporary capitalism; as well as the contributions of a research recording and of two book reviews on economic agencies and pedagogies and the financialization of everyday life.
Keywords: DALE, Gareth; Karl Polanyi; capitalism; democracy; market

The unfinished development of the frontier: a Karl Polanyi reading of the conflict between the forestry industry, Mapuche communities and the Chilean State - Undurraga, Tomás; Márquez, Felipe (Sociologia & Antropologia, 2021)
Resumo O artigo explora conflitos entre a indústria florestal, as comunidades Mapuche e o Estado chileno à luz da leitura de Polanyi sobre a expansão capitalista. Oferece análise histórico-institucional das maneiras pelas quais o Estado chileno usou a florestação para domar uma fronteira selvagem e os povos nativos que ali vivem. Argumenta que o aumento da violência nessa zona responde à crescente militarização do Estado na área e reflete o contramovimento de proteção social iniciado pelo povo Mapuche - contra uma indústria florestal de livre mercado que transformou a paisagem, limitando o acesso dos Mapuche a terras e florestas, e contra um processo de modernização liderado pelo Estado chileno que corroeu as instituições tradicionais dos Mapuche e lhes ofereceu integração em termos desiguais, como “campesinos pobres”.
Keywords: Chile; Estado chileno; Mapuche; Polanyi; contramovimento; countermovement; forest industry; indústria florestal; proteção social; social protection

Cucumbers and Courgettes: Rural Workfare and the New Double Movement in Hungary - Hann, Chris (Intersections. East European Journal of Society and Politics, 2016)
The paper is an application of the economic anthropology of Karl Polanyi to contemporary rural Hungary. After addressing the influence of Polanyi’s critique of market society and his standing in the discipline of anthropology, the main focus is the community of Tázlár on the Danube-Tisza interfluve. The paper traces the history of the ‘fictitious commodities’ of land and labour in this relatively isolated settlement, which was not fully integrated into the national society until the socialist era. The innovative symbiosis of household and cooperative farming was destroyed in the 1990s. In the depressed economic climate of today, workfare schemes are popular because they treat villagers as human beings rather than as commodities to be exploited for maximum profit. The workfare initiatives of populist power holders can be interpreted as one facet of a complex ‘double movement’ in which postsocialist society seeks to defend itself against the domination of the market.
Keywords: (post)socialism; Danube-Tisza interfluve; Hungary; Karl Polanyi; double movement; fictitious commodities; neoliberalism; workfare